Nocardia rubra cell wall skeleton-induced MARCO expression: implications for improved phagocytosis and cytokine secretion in tumor-associated macrophages - Zhou, Guiyuan; Chen, Wei; Dong, Xiaomin; Guo, Qianyu; Bai, Xue; Zheng, Yan; Zhang, Lei; Shao, Suxia (Frontiers in Immunology, 2026)
IntroductionNocardia rubra cell wall skeleton (Nr-CWS) demonstrates a significant therapeutic effect against human papillomavirus (HPV) infection, but its precise immunomodulatory mechanisms warrant further investigation. This study investigates how Nr-CWS influences tumor-associated macrophages (TAMs) immune functions through macrophage receptor with collagenous structure (MARCO)-mediated mechanisms.MethodsCervical tissues of three cervical intraepithelial neoplasia (CIN) patients receiving Nr-CWS monotherapy and HPV infection turning negative were collected before and after treatment, and gene microarray analysis was performed. MARCO expression and immune cell infiltration were further analyzed using transcriptomic data from 33 tumor types in The Cancer Genome Atlas (TCGA). In vitro, TAMs derived from Human Monocytic Leukemia Cell Line 1 (THP-1) cells were treated with Nr-CWS, and changes in MARCO expression, cytoskeletal rearrangement, pseudopod length, lysosome count, and cytokine secretion were assessed. MARCO inhibition experiments were also performed.ResultsGene microarray revealed significant upregulation of MARCO, a key phagosome pathway gene, post-treatment. TCGA analysis indicated that MARCO expression is significantly altered in most tumor tissues compared to normal tissues and is associated with the infiltration of multiple immune cell types, with a particularly strong correlation to macrophage abundance. Histologically, Nr-CWS increased MARCO⁺ macrophages in cervical tissues. In vitro, Nr-CWS elevated MARCO expression in TAMs, enhanced pseudopod formation, lysosome number, cytoskeleton reorganization, and promoted proinflammatory cytokine secretion. Conversely, MARCO inhibition suppressed these immune functions.DiscussionThe study demonstrates that Nr-CWS enhances TAM anti-tumor immune function via MARCO upregulation, leading to improved phagocytic activity and proinflammatory response. These findings align with genomic and cellular evidence, suggesting MARCO as a key mediator in Nr-CWS-induced macrophage reprogramming, with implications for HPV-related neoplasia immunotherapy.